2018
DOI: 10.3892/etm.2018.6272
|View full text |Cite
|
Sign up to set email alerts
|

Decreased microRNA‑140‑5p contributes to respiratory syncytial virus disease through targeting Toll‑like receptor 4

Abstract: Abstract. The abnormal expression of miRNAs (miRs) has previously been reported in respiratory syncytial virus (RSV) disease. However, to the best of our knowledge, the expression of miR-140-5p in patients with an RSV infection has never been explored. Reverse transcription-quantitative polymerase chain reaction was performed to analyze the level of miR-140-5p in the blood and nasopharyngeal airway samples. ELISAs were performed to determine the levels of tumor necrosis factor α, interleukin (IL)-1β, IL-6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Emerging evidence indicates that silencing RHBDD1 suppresses cell growth and proliferation in hepatocellular carcinoma [13], glioblastoma [14] and colorectal cancer [15]. In breast cancer [16,17] and colorectal cancer cells [18], RHBDD1 has been shown to promote migration, invasion and EMT. However, there are few reports on the impact of RHBDD1 on the EMT of NSCLC cells and the associated mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence indicates that silencing RHBDD1 suppresses cell growth and proliferation in hepatocellular carcinoma [13], glioblastoma [14] and colorectal cancer [15]. In breast cancer [16,17] and colorectal cancer cells [18], RHBDD1 has been shown to promote migration, invasion and EMT. However, there are few reports on the impact of RHBDD1 on the EMT of NSCLC cells and the associated mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the negative miRNA-mRNA network revealed 12 significantly down-regulated miRNAs targeting these TLRs. It has been reported that some miRNAs, like miR-140-5p and welldescribed miR-155, could target TLRs to regulate the innate immune response during the virus infection that had subsequent impact on virus replication [38][39][40]. Upon recognition of pathogens, TLRs recruit a specific set of adaptor molecules, such as MyD88 (myeloid differentiation factor 88) and TIRAP, then initiate downstream signaling events that leads to the secretion of inflammatory cytokines, type I IFN, chemokines, and antimicrobial peptides [41].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the negative miRNA-mRNA network revealed 12 significantly down-regulated miRNAs targeting these TLRs. It has been reported that some miRNAs, like miR-140-5p and well-described miR-155, could target TLRs to regulate the innate immune response during the virus infection that had subsequent impact on virus replication [38][39][40]. Upon recognition of pathogens, TLRs recruit a specific set of adaptor molecules, such as MyD88 (myeloid differentiation factor 88) and TIRAP, then initiate downstream signaling events that leads to the secretion of inflammatory cytokines, type I IFN, chemokines, and antimicrobial peptides [41].…”
Section: Discussionmentioning
confidence: 99%